Management of white rot of pea incited by (Sclerotinia sclerotiorum) using Trichoderma spp. and biopesticides - A.S. KAPOOR*, R. KAPIL and (Indian Phytopathology, 2005)
Volatile and non-volatile metabolites of all the bioagents (Trichoderma spp.) significantly reduced the mycelial growth and germination of Sclerotinia sclerotiorum. Among the delivery systems evaluated for controlling the white rot, sodium alginate pellet formulation (800 No./m2) followed by soil application of wheat bran based Trichoderma viride formulation @ 11.2g/m2were found most effective delivery systems. Six neem based biopesticides were evaluated at two concentrations (0.5 and 0.1%) against S. sclerotiorum. Results revealed, Wanis as the most effective at both the concentrations followed by Neemgold. Out of eight organic substrates evaluated for mass multiplication of bioagents, maximum multiplication of bioagents was found in FYM followed by in Lantana camara and wheat bran. Population dynamics studies of T. viride revealed significant increase in population even after 60 days of application of bioagent.